We are given the following functions
![f\mleft(x\mright)=6x+7\qquad g(x)=-2x-4\qquad h(x)=-(3x)/(4)](https://img.qammunity.org/2023/formulas/mathematics/college/3r8l5vnx2owvldfkc8gvkchgcbts34ypte.png)
We are asked to find out g(-6) and h(-12)
1. g(-6)
it simply means that we have to plug x = -6 into the function of g(x)
![\begin{gathered} g(x)=-2x-4 \\ g(-6)=-2(-6)-4 \\ g(-6)=12-4 \\ g(-6)=8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8629f4uriqofrv73pmk61zm5x3nlyv7bvu.png)
Therefore, g(-6) = 8
2. h(-12)
Once again we have to plug x = -12 into the function of h(x)
![\begin{gathered} h(x)=-(3x)/(4) \\ h(-12)=-(3(-12))/(4) \\ h(-12)=(36)/(4) \\ h(-12)=9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3mmvxh67speavlc9t4anem74psi3qj1hbv.png)
Therefore, h(-12) = 9